Incubation period for outbreak-associated, non-typhoidal salmonellosis cases, Minnesota, 2000–2015. Issue 4 (7th February 2018) - Eikmeier, D.; Medus, C.; Smith, K.
Abstract: Incubation period for non-typhoidal Salmonella (NTS) infections is generally reported as 6–72 h despite numerous reports of foodborne NTS outbreaks with median incubation periods >3 days. We summarised 16 years of Minnesota foodborne NTS outbreaks to better estimate the expected range of incubation periods for NTS infections. Of the 1517 NTS outbreak cases, 725 had enough data to calculate a precise incubation period. The median incubation period was 45 h; 77 (11%) cases had incubations ⩽12 h and 211 (29%) cases had incubations >72 h. Incubation period length varied by outbreak vehicle type, Salmonella serotype and outbreak setting. Based on our data, a more accurate description would be that the incubation of NTS infection is usually from 12 to 96 h, that incubations in >96 to 144 h (>4 to 6-day) range are not unusual and that incubations from 7 to 9 days and occasionally longer also occur.